2008
DOI: 10.3748/wjg.14.6318
|View full text |Cite
|
Sign up to set email alerts
|

Different effects of ghrelin, des-acyl ghrelin and obestatin on gastroduodenal motility in conscious rats

Abstract: Fujimiya M, Asakawa A, Ataka K, Kato I, Inui A. Different effects of ghrelin, des-acyl ghrelin and obestatin on gastroduodenal motility in conscious rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 29 publications
0
21
0
2
Order By: Relevance
“…The effects of peripheral obestatin on the duodenum, but not on the antrum, were abolished by perivagal capsaicin treatment, whereas intracerebroventricular injection of the selective CRF 1 -R and CRF 2 -R antagonists blocked the suppressive effects of intravenous obestatin on the antrum and duodenum. Collectively, these results imply that the inhibitory actions of peripheral obestatin on fed gastroduodenal motility required brain CRF 1 -R and CRF 2 -R, and vagal afferent pathways might be partially involved Fujimiya et al, 2008) (see Tables 2 and 3). In contrast, intraperitoneal obestatin did not affect gastric emptying parameters and did not inhibit the prokinetic effects of acyl ghrelin (De Smet et al, 2007).…”
Section: Normal Physiology and Pathophysiology Of Ghrelin Gene mentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of peripheral obestatin on the duodenum, but not on the antrum, were abolished by perivagal capsaicin treatment, whereas intracerebroventricular injection of the selective CRF 1 -R and CRF 2 -R antagonists blocked the suppressive effects of intravenous obestatin on the antrum and duodenum. Collectively, these results imply that the inhibitory actions of peripheral obestatin on fed gastroduodenal motility required brain CRF 1 -R and CRF 2 -R, and vagal afferent pathways might be partially involved Fujimiya et al, 2008) (see Tables 2 and 3). In contrast, intraperitoneal obestatin did not affect gastric emptying parameters and did not inhibit the prokinetic effects of acyl ghrelin (De Smet et al, 2007).…”
Section: Normal Physiology and Pathophysiology Of Ghrelin Gene mentioning
confidence: 99%
“…Pharmacological blockage revealed both CRF 1 -R and CRF 2 -R responsible for the activation of obestatin actions on the brain. Immunohistochemical analysis demonstrated that CRFand urocortin-2-containing neurons in the paraventricular nucleus in the hypothalamus were activated by intravenous injection of obestatin in rats Fujimiya et al, 2008). However, another study claimed that intraperitoneal administration of obestatin did not elicit c-fos immunoreactivity in ingestive behavior-relevant brain nuclei in rodents .…”
mentioning
confidence: 99%
“…In vitro, ghrelin contracts muscle strips of rat forestomach and antrum (7,15). Ghrelin administration induces dose-dependent phase III-like contractions in the antrum and increases the motility index (MI) in rodents (11,45,52) and humans (42). In addition, treatment with ghrelin and GH-releasing peptide-6, which is an agonist of ghrelin receptors, improves delayed gastric emptying in mice administered with cisplatin (28) and diabetic mice with gastroparesis (37).…”
mentioning
confidence: 99%
“…As such, ghrelin would be an important new target for the development of treatments for obesity. Ghrelin administration induces dose-dependent contractions in the antrum and increases the motility in rodents and humans (14,15). Also the potential of the ghrelin system as a therapeutic target for obesity treatment is still under discussion.…”
Section: Discussionmentioning
confidence: 99%